2019
DOI: 10.1002/ejoc.201900815
|View full text |Cite
|
Sign up to set email alerts
|

Convergent Synthesis of the Hexasaccharide Repeating Unit of the O‐Antigenic OPS of Escherichia coli O133

Abstract: Synthesis of the hexasaccharide repeating unit of the O‐antigen from E. coli O133 has been accomplished with rational protecting group manipulations on commercially available monosaccharides and stereoselective glycosylations through a convergent protocol. A late stage TEMPO mediated oxidation is used to install the required uronic acid moiety. Chloroacetate group is used extensively as a temporary protecting group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…The synthetic investigation commenced with the syntheses of donors 2 , 2′ , and 4 (Scheme ). Under the combined effect of NIS/TMSOTf, the coupling between 5 and 6 smoothly proceeded, affording disaccharide 7 as a mixture of α/β stereoisomers, with the desired α-isomer remarkably predominating due to the favorable LDP effect of the C-6 benzoyl (Bz) group in 5 (90%, α/β 7:1, J = 3.6 Hz for the α-isomer). Unifying the protecting groups (PGs) of 5 to the benzoyl group was conducted via a sequence of benzyl and benzylidene group removal under hydrogenolysis conditions and benzoylation under conventional conditions (BzCl, pyridine, 0 °C to rt).…”
Section: Results and Discussionmentioning
confidence: 99%
“…The synthetic investigation commenced with the syntheses of donors 2 , 2′ , and 4 (Scheme ). Under the combined effect of NIS/TMSOTf, the coupling between 5 and 6 smoothly proceeded, affording disaccharide 7 as a mixture of α/β stereoisomers, with the desired α-isomer remarkably predominating due to the favorable LDP effect of the C-6 benzoyl (Bz) group in 5 (90%, α/β 7:1, J = 3.6 Hz for the α-isomer). Unifying the protecting groups (PGs) of 5 to the benzoyl group was conducted via a sequence of benzyl and benzylidene group removal under hydrogenolysis conditions and benzoylation under conventional conditions (BzCl, pyridine, 0 °C to rt).…”
Section: Results and Discussionmentioning
confidence: 99%
“…1 H NMR (CDCl 3 , 500 MHz) δ: 7.85-7.09 (m, 19H), 5.60 (s, 1H), 5.33 (dd, 1H, J 1.5 Hz, 3.0 Hz), 5.30 (d, 1H, J 8.5 Hz), 5.27 (s, 1H), 5.26 (d, 1H, J 1.5 Hz), 5.12 (bs, 1H), 5.01, 4.92 (2d, 2H, J 12.5 Hz), 4.79 (t, 1H, J 10.0 Hz), 4.40 (dd, 1H, J 5.0 Hz, 10.5 Hz), 4.32 (dd, 1H, J 8.5 Hz, 10.5 Hz), 3.94 (dd, 1H, J 3.0 Hz, 10.5 Hz), 3.81 (m, 4H), 3.67 (m, 3H), 3.46 (m, 2H), 3.28 (m, 2H), 3.17 (m, 1H), 2.76 (bs, 1H), 2.06 (s, 3H). 13 p-Methoxyphenyl 2,3-O-isopropylidene-3-oxo-α-L-rhamnopyranoside (9). To a solution of the known compound 8 (3.5 g, 11.3 mmol) in dry (CH 2 ) 2 Cl 2 (35 mL), the Dess-Martin periodinane (5.25 g, 12.4 mmol) was added and the mixture was refluxed for 1 hour when TLC (n-hexane-EtOAc; 2 : 1) showed complete conversion of the starting material to a faster moving spot.…”
Section: Papermentioning
confidence: 99%
“…5 Recently, Perepelov et al reported the structure of the O-antigen from E. cloacae G3422 along with the gene cluster involved in the genesis of the said O-antigen. 6 In continuation of our efforts towards the chemical synthesis of bacterial oligosaccharides, [7][8][9][10] herein we report a convergent route towards the successful synthesis of the tetrasaccharide repeating unit of the O-antigen from E. cloacae G3422 in the form of its 2-aminoethyl glycoside (1, Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…The 2-aminoethyl glycoside at the reducing end will facilitate further glycoconjugate formation without hampering the stereochemistry of the anomeric center. We have used similar glycosides in case of other chemically synthesized oligosaccharides before [810]. The corresponding aminopropyl linker has also been used by others [11].…”
Section: Introductionmentioning
confidence: 99%